Between the network and the narrative: transmedia storytelling as a philosophical lens for creative writers. Issue 2 (3rd May 2016) - Lynch, Daniel
ABSTRACT: Over the last decade, the traction gained by transmedia storytelling (TS) in increasingly varied academic disciplines, and in the practice of storytellers, has led to a rupturing of the boundaries between discursive territories and narrative practices. The rupturing force, as it were, can be seen as the influence of emerging networked technologies, and the widening gyre of convergence culture on the practice of storytelling, and the resulting attempts to understand the critical value of works experimenting in this space. In the absence of a robust framework that accounts for interdisciplinary, intersecting, and experimental practices that are often mobilised in TS works, this paper asserts that TS is best understood as a philosophical lens through which the nexus of text and technology, narrative and network, might be mediated, pulling into focus the liminality at intersecting storytelling practices and the networks which allow the telling to occur. The practice of creative writing, in particular, benefits from this framing, as it encourages innovation in a field where interest in large scale film and television properties overshadow much of the significant work being conducted by creative writers.